A Chinese premature infant with cleidocranial dysplasia characterized by heterozygous RUNX2 mutation and cerebral infarction: a case report - Zhao, Wuyun; An, Yanbin; Zhang, Xiaoyan; Zhuo, Na; Cai, Cheng; Arigong, Gaowa (Frontiers in Pediatrics, 2025)
IntroductionCleidocranial dysplasia (CCD) is a rare genetic skeletal disorder with a low incidence rate. This study reports the first documented case in Inner Mongolia, involving a premature male newborn with a history of birth asphyxia and cerebral infarction. The patient exhibited characteristic clinical features, including abnormal cranial suture palpation, hypertelorism, depressed nasal bridge, and shortened limbs, leading to genetic testing that identified a heterozygous mutation in the RUNX2 gene—the known cause of CCD.MethodsClinical examination included detailed physical assessment, cranial MRI, CT scan with 3D reconstruction, and chest X-ray. Genetic analysis was performed to detect mutations in the RUNX2 gene. Imaging results revealed significantly widened cranial sutures, open fontanelles, partial skull defects, right clavicular hypoplasia, and reduced bone density.ConclusionGenetic testing confirmed a heterozygous pathogenic variant in the RUNX2 gene, consistent with a diagnosis of cleidocranial dysplasia. This case represents the first reported instance of CCD in Inner Mongolia.DiscussionThis case underscores the importance of recognizing the clinical and genetic features of RUNX2-related CCD to facilitate early and accurate diagnosis. The findings aim to enhance clinical awareness of this rare condition, particularly in regions where it has not been previously reported, and to promote timely intervention and genetic counseling.